CHARACTERIZATION OF BLUE AND WHITE VARIETIES OF CLITORIA TERNATEA (L.) BASED ON SEED PROTEIN PROFILING COLLECTED FROM NORTH INDIA - TARA CHANDRA RAM,; BIJOY K. ROY, (International Journal of Pharma and Bio Sciences, 2015)
The medicinal plant Clitoria ternatea belongs to the family fabaceae and their seeds are highly nutritive. In the present study characterization of seed proteins of its popularly growing varieties has been undertaken. A comparative study has been done in term of qualitative estimation of total seed protein among the six accessions of white and blue petal varieties. Three accessions (ACCRI, ACCR2 and ACCR3) of blue petal variety and three accessions (ACCR4, ACCR5 and ACCR6) of white petal variety were taken. With the help of protein molecular markers and electrophoresis pattern, seed proteins of above two varieties showed the presence of four categories of polypeptide masses. Some bands were seen in both the varieties shows varietal differences and genetic composition. A dendrogram was made using UPGMA which revealed the interrelationship of two varieties of Clitoria that indicates two clustures viz. clusture A and clusture B. Clustures A suggested that there are no changes in protein profiling among ACCR1, ACCR2 and ACCR3, but different with protein profiling among clusture B (ACCR4, ACCR5 and ACCR6).